1998
DOI: 10.1111/j.1741-2358.1998.00079.x
|View full text |Cite
|
Sign up to set email alerts
|

Maryland veterans' knowledge of risk factors for and signs of oral cancers and their use of dental services

Abstract: Veterans at higher risk for oral cancers were less likely to have visited the dentist in the previous year, and, overall, were ill informed and misinformed about these cancers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2000
2000
2013
2013

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 21 publications
1
7
0
Order By: Relevance
“…This concurs with other studies done worldwide (Canto et al, 1998;Warnakulasuriya et al, 1999;Cruz et al, 2002;West et al, 2006;Prayman et al, 2009). Students were significantly most aware about the adverse effects of smoking than working adults.…”
Section: Discussionsupporting
confidence: 82%
“…This concurs with other studies done worldwide (Canto et al, 1998;Warnakulasuriya et al, 1999;Cruz et al, 2002;West et al, 2006;Prayman et al, 2009). Students were significantly most aware about the adverse effects of smoking than working adults.…”
Section: Discussionsupporting
confidence: 82%
“…A recent qualitative investigation showed dentists were hesitant to mention that an oral cancer examination was provided to their patients unless the practitioners found a suspicious lesion (21). In addition, the public's poor knowledge of the risk factors and signs and symptoms of oral cancer (22)(23)(24)(25)(26) might have led them to believe an examination was unnecessary (27).…”
Section: To 3 Times Per Person Per Yearmentioning
confidence: 99%
“…More recently, a small survey of Maryland veterans in 1998 reported that 84% recognised tobacco use as a risk factor for oral cancer but only 39% identified alcohol. 10 Information is similarly scarce on the extent to which health professionals such as GPs or dentists raise the topic with high risk groups. A UK survey of dentists undertaken in 1991 found that 84% of respondents claimed to perform screening of the oral mucosa regularly.…”
Section: Introductionmentioning
confidence: 99%